Biosensors - Recent Advances and Future Challenges - Katz, Evgeny; Bollella, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The present book is devoted to all aspects of biosensing in a very broad definition, including, but not limited to, biomolecular composition used in biosensors (e.g., biocatalytic enzymes, DNAzymes, abiotic nanospecies with biocatalytic features, bioreceptors, DNA/RNA, aptasensors, etc.), physical signal transduction mechanisms (e.g., electrochemical, optical, magnetic, etc.), engineering of different biosensing platforms, operation of biosensors in vitro and in vivo (implantable or wearable devices), self-powered biosensors, etc. The biosensors can be represented with analogue devices measuring concentrations of analytes and binary devices operating in the YES/NO format, possibly with logical processing of input signals. Furthermore, the book is aimed at attracting young scientists and introducing them to the field, while providing newcomers with an enormous collection of literature references.